2012
DOI: 10.1007/s11262-012-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan

Abstract: The genome of Banana bunchy top virus (BBTV) consists of six segments of single-stranded DNA of approximately 1 kb in length. We identified and sequenced the complete genomes of two BBTV isolates, one with and one without satellite DNA, from Haikou, Hainan, China. The Haikou-2 isolate contains six genomic segments and an additional satellite DNA while the Haikou-4 isolate contains only six genomic segments. Typical of other babuviruses, each genomic segment encodes a single open reading frame and contains the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
5
28
1
Order By: Relevance
“…However, some contained 1037 nt. Previous studies showed that the position of the start codon of ORF encoded by DNA-U3 was UUG instead of AUG as observed in some Chinese isolates, and that all isolates have a smaller putative ORF with a GUG start codon located downstream (Yu et al 2012). Since all Sumatra isolates had a UUG codon in position 143-145 instead of AUG as in an Australian and some Chinese isolates, GUG could be considered as the start codon.…”
Section: Resultsmentioning
confidence: 90%
“…However, some contained 1037 nt. Previous studies showed that the position of the start codon of ORF encoded by DNA-U3 was UUG instead of AUG as observed in some Chinese isolates, and that all isolates have a smaller putative ORF with a GUG start codon located downstream (Yu et al 2012). Since all Sumatra isolates had a UUG codon in position 143-145 instead of AUG as in an Australian and some Chinese isolates, GUG could be considered as the start codon.…”
Section: Resultsmentioning
confidence: 90%
“…BBTV isolates that have genome components derived from two or more different parental viruses have been inferred using a variety of phylogenetic (Hu et al. 2007; Yu et al. 2012) and statistical recombination detection methods (Martin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was isolated from a monocotyledonous host. Two geminialphasatellites have been isolated from monocotyledonous plants and both of these have features typical of the Geminialphasatellitinae [24]; and twelve have been isolated from bananas and cardamom, all of which have similarities to other nanoalphasatellites [2,11,18,25,53]. We therefore propose this molecule to represent an unassigned species in the family Alphasatellitidae.…”
Section: Unassigned Species In the Family Alphasatellitidaementioning
confidence: 91%